2009
DOI: 10.1007/s11258-009-9595-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition and rhizome severing modify clonal growth and reproductive modes of Leymus chinensis population

Abstract: We examined the effects of N addition and rhizome severing on sexual and clonal reproduction and their trade-off in a rhizome clonal grass, Leymus chinensis (Trin.) Tzvel. We discovered that N addition not only greatly increased the quantity and biomass of Leymus chinensis ramets, but also promoted ramet production by increasing the tillers of the plant, while abated the other alternative clonal propagation strategy of rhizome elongation. However, N addition did not affect the rhizome biomass and it significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
(41 reference statements)
2
57
1
Order By: Relevance
“…Our results indicated that once the clonal production of S. alterniflora associated with short-distance spread was inhibited by the surrounding physical environmental stress, the sexual production would be promoted to benefit long-distance dispersal, which would increase the probability to occupy more suitable habitats. However, similar to an earlier study in a rhizome clonal grass Leymus chinensis (Bai et al, 2009), we observed that rhizome fragmentation did not affect the reproductive strategy.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that once the clonal production of S. alterniflora associated with short-distance spread was inhibited by the surrounding physical environmental stress, the sexual production would be promoted to benefit long-distance dispersal, which would increase the probability to occupy more suitable habitats. However, similar to an earlier study in a rhizome clonal grass Leymus chinensis (Bai et al, 2009), we observed that rhizome fragmentation did not affect the reproductive strategy.…”
Section: Discussionsupporting
confidence: 91%
“…In the temperate semi-arid steppes of North China, the Leymus chinensis community and Stipa grandis community are two generally known steppes widely distributed on the Mongolian plateau (Li 1988). L. chinensis, possessing long strong rhizomes and vigorous vegetative propagation, gives rise to extensively spreading clones and often forms monodominant stands (Bai et al 2009). S. grandis, however, is a type of perennial tussock grass completely different from L. chinensis (Zhao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that allow S. alterniflora to adapt to high salinity conditions, such as germination, growth, reproduction, morphology and physiology, have been well documented (Brown and Pezeshki, 2007;Brown et al, 2006;Hester et al, 2001;Vasquez et al, 2006;Wang et al, 2010). Since resources for metabolism and biomass gain are limited, increasing resource allocation to one function may reduce that to other functions (Bai et al, 2009;Liu et al, 2009). Reduced growth in response to increased sexual production has been known for many species (Snow and Whigham, 1989;Stark et al, 2009;Thiele et al, 2009).…”
Section: Introductionmentioning
confidence: 99%